Is platelet-rich plasma effective in treating uterine inflammation in jennies inseminated with cryopreserved donkey semen? - Freitas, Marcela Souza e; García, Henry David Mogollón; Fiala-Rechsteiner, Sandra Mara da Encarnação; Fontes, Carolina Silveira; Teixeira, Cristian Silva; Viana, João Henrique Moreira; Albino, Matheus Vilela; Costa, Lorraine Marcele Lopes da; Carneiro, Gustavo Ferrer; Ribeiro, Gabriella Costa [UNESP]; Sancler-Silva, Yame Fabres Robaina (Elsevier, 2025)
Despite frozen donkey semen demonstrating high quality after thawing and achieving suitable pregnancy rates in mares, it yields unsatisfactory results in jennies, likely due to a stronger uterine inflammatory response. This study assessed the effects of platelet-rich plasma (PRP) on uterine inflammation and pregnancy rates in jennies inseminated with frozen donkey semen. Estrous cycles from 11 jennies were assigned to three groups: Control (CTR, n = 22) with no treatment; Single PRP infusion (S-PRP, n = 22) administered 30 h after ovulation induction, prior to artificial insemination (AI); and Double PRP infusion (D-PRP, n = 21) with the first infusion at 30 h after ovulation induction and the second 4 h after AI. Insemination was performed with frozen donkey semen (1 billion sperm) deposited deeply in the uterine horn immediately after ovulation. Endometrial edema, intrauterine fluid (IUF), uterine vascularization, and endometrial cytology were evaluated pre-AI (TCt) and post-AI (6, 24, and 48 h). Uterine biopsies were taken at T48 for histopathological and collagen evaluation. Peripheral blood samples were collected on D5 for serum progesterone measurement, and pregnancy was evaluated via ultrasonography on D14. Data were analyzed using GLMMs, ANOVA, Friedman, and Kruskal-Wallis tests in SAS and GraphPad Prism, with significance set at p < 0.05. The S-PRP group showed less IUF accumulation than the CTR group at T6. Other parameters showed no significant differences among the groups. Cytology revealed a high percentage of inflammatory cells at T6 in all groups, which decreased in subsequent evaluations. In the CTR group, neutrophil percentages were similar to TCt at T24, while treated groups reached this similarity only by T48. Eosinophil percentages increased over time only in the treated groups. Pregnancy rates showed no differences among the groups (CTR: 0 %, S-PRP: 0 %, D-PRP: 10 %). Results indicate that PRP treatments were ineffective in modulating uterine inflammation and did not enhance pregnancy rates in jennies inseminated with frozen donkey semen.
Keywords: Endometritis; Fertility; Frozen semen; Jackass; PRP